2006
DOI: 10.1021/bm060342i
|View full text |Cite
|
Sign up to set email alerts
|

Slow Digestion Property of Native Cereal Starches

Abstract: The slow digestion property of native cereal starches, represented by normal maize starch, was investigated. The in vitro Englyst test showed that 53.0% of the maize starch is slowly digestible starch (SDS), and scanning electron microscopy (SEM) revealed that SDS starts from an increase of pore size until almost complete fragmentation of starch granules. However, similar amounts of SDS ( approximately 50%) were shown for partially digested fragmented starch residuals, which would normally be considered resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
271
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 390 publications
(309 citation statements)
references
References 27 publications
34
271
4
Order By: Relevance
“…Nevertheless, Hylon V provided from HMT did not achieve quite high RS content. This phenomenon might suggest that the particle surfaces of Hylon V, unlike that of ordinary corn starch, were lack of some tiny holes and the interiors of the particles were without a large number of channels for amylase entering (Zhang et al, 2006). Hence, the disadvantage of the Hylon V caused some difficulties for amylase hydrolysis that occurred only on the surface of the starch granules not inside.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Hylon V provided from HMT did not achieve quite high RS content. This phenomenon might suggest that the particle surfaces of Hylon V, unlike that of ordinary corn starch, were lack of some tiny holes and the interiors of the particles were without a large number of channels for amylase entering (Zhang et al, 2006). Hence, the disadvantage of the Hylon V caused some difficulties for amylase hydrolysis that occurred only on the surface of the starch granules not inside.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was terminated by boiling for 20 min. The hydrolysed samples containing α-limit dextrins were analysed for their apparent molar mass by HPSEC-RI (Zhang, Ao and Hamaker, 2006) using pullulans as standard (Polymer Laboratories Inc. Amherst, MA).…”
Section: Hydrolysis Properties By Human Pancreatic α-Amylasementioning
confidence: 99%
“…Susceptibility of starch to enzyme attack is influenced by several factors, such as granule size and available specific surface (Franco et al, 1992(Franco et al, , 1998Knutsonetal., 1982;Tahir etal., 2010;Tangetal.,2004),surfaceporosityandchannels (FaIllionetal., 1992(FaIllionetal., , 1993SujkaandJamroz, 2007;Zhang et al, 2006;), amylose and amylopectin content (Blazeck and COpelaIld, 2010;Hoover and Manuel, 1995;Hoover and Sosulski, 1985;Holm aIld Bjorck, 1988;Ring et al, 1988),crystallinestructure(Chungetal.,2010Zhouetal.,2004;Gunaratneand Hoover, 2002), extent of branching (long a.I11ylopectin branchesibraIlch density) (Dona eta1.,2010;Shresthaet al, 2010), distribution pattem ofa-(l,6) branch points between the amorphous aIld crystalline regions (Gunaratne and Hoover, 2002;Janeetal., 1997), degree of crystallinity (Chungetal., Zhou et al, 2004), packing of polymers within granules (dense/loose), helical conformation ofa.I11ylose molecules (Shrestha et al, 2010), presence of non-starch substances (proteins, lipids and phosphorus) (HooveraIld Manuel, 1995;Perera and Hoover, 1998) and inhibitors (Colonna et al, 1992;Zhou et al, 2004). The kinetics of a-amylolysis of granular and gelatinized starch are characterized by an initial rapid hydrolysis phase followed by a slower phase.…”
Section: Enzymebydrolysisofnativestarcbesmentioning
confidence: 99%
“…However, Zhang et al (2006) have shown in studies on cereal starches, that the amorphous and crystalline regions are digested simultaneously. A side-by-side and even digestion mechanism that starts from the channels was proposed as the mechanism leading to the simultaneous digestion of crystalline and amorphous regions.…”
Section: Chairmentioning
confidence: 99%